2011
DOI: 10.1002/ijc.26083
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation and expression of MGMT and the DNA mismatch repair genes MLH1, MSH2, MSH6 and PMS2 in paired primary and recurrent glioblastomas

Abstract: Epigenetic silencing of the O 6 -methylguanine-DNA methyltransferase (MGMT) gene promoter is associated with prolonged survival in glioblastoma patients treated with temozolomide (TMZ). We investigated whether glioblastoma recurrence is associated with changes in the promoter methylation status and the expression of MGMT and the DNA mismatch repair (MMR) genes MLH1, MSH2, MSH6 and PMS2 in pairs of primary and recurrent glioblastomas of 80 patients, including 64 patients treated with radiotherapy and TMZ after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
182
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 266 publications
(205 citation statements)
references
References 36 publications
20
182
1
2
Order By: Relevance
“…26 Meanwhile many tools are available to increase the extent of resection while keeping the risk of new neurological deficits low.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
See 1 more Smart Citation
“…26 Meanwhile many tools are available to increase the extent of resection while keeping the risk of new neurological deficits low.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
“…[15][16][17][18][19] The demonstration of promoter methylation of the MGMT gene assessed by methylation-specific PCR or pyrosequencing of bisulfite-modified DNA is associated with superior outcome in anaplastic glioma patients treated with radiotherapy or alkylating agent chemotherapy 19,20 and with specific benefit from temozolomide (TMZ) in glioblastoma patients. [21][22][23][24] Retesting the MGMT status at recurrence is not necessary since the methylation status remains stable, at least in glioblastoma, 25,26 …”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…Temporal heterogeneity of MGMT methylation is conceivable; however, matched primary GBM and their recurrences have largely revealed identical MGMT status, and retesting is currently discouraged in clinical guidelines (35). Loss of chromosome 10q has also been considered a factor influencing MGMT methylation, but recent studies found no correlation between MGMT copy number and extent of methylation in GBM (32) or low-grade gliomas (36).…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating MGMT promoter methylation within glioblastoma lesions as well as in paired primary and recurrent glioblastoma samples suggested that MGMT promoter methylation could be a homogeneous marker throughout malignant gliomas (48) and that most recurrent lesions retained the methylation profile from the primary lesions (49). However, considering the increasing awareness of tumor heterogeneity (50) and the positive predictive value (77%) for serum assay observed in our study, the serum methylation assay may provide a possible alternative for patients with no available tumor samples.…”
Section: Discussionmentioning
confidence: 99%